Juvenile dispersal behaviour and conspecific attraction: an alternative approach with translocated Spanish imperial eagles. (June 2016) - Muriel, Roberto; Morandini, Virginia; Ferrer, Miguel; Balbontín, Javier; Morlanes, Viviane
Abstract : The transient stage prior to definitive recruitment, known as juvenile dispersal, is thought to be under great evolutionary pressure and subject to a trade-off between associated costs and long-term benefits for fitness. Conspecific attraction has been shown to be an adaptive mechanism driving dispersal behaviours that may lead to negative density-dependent dispersal patterns. However, conspecific attraction can be scarcely discernible from imprinting to the natal area in wild populations. Reintroductions in the absence of settled individuals can be used as alternative colonization-like contexts to investigate the relative role of conspecific attraction in juvenile dispersal behaviours. We examined the spatiotemporal development of dispersal movements in reintroduced juveniles of a long-lived species with deferred maturity, the Spanish imperial eagle, Aquila adalberti, in comparison with nonmanipulated juveniles from a nearby population. We found that reintroduced birds started dispersal earlier and were initially more philopatric, probably encouraged by the advantageous competitive environment in the release area. Conversely, they revealed a more expansive strategy as they matured and approached the time when settlement decisions would be made, especially in females. They returned less frequently, increased exploratory movements and dispersal ranges, and visited breeding areas, probably as a consequence of the relatively lower reproductive prospects in the release area than in nearby populations. Therefore, the singular social cueing in reintroductions may eventually lead to juvenile wandering behaviours characteristic of colonization contexts in this territorial long-lived species. Such dispersive strategies relying on conspecifics may have important consequences for population dynamics and management. They may hinder the initial settlement phase in reintroductions, although behaviours such as longer returns may enhance recruitment prospects. Translocation programmes should consider specific dispersal scenarios, as well as postrelease monitoring to increase philopatry and success probabilities. Highlights: We investigate the role of conspecific attraction on juvenile dispersal behaviours. Dispersal movements of translocated and nonmanipulated individuals were compared. Translocated individuals revealed a more dispersive strategy as they matured. Lower reproductive prospects in the release area may lead to expansive strategies. Colonization-like dispersal may hinder the establishment phase in reintroductions.